2015
DOI: 10.4103/2249-4863.152250
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and sociodemographic risk factors of enuresis nocturna among elementary school-age children

Abstract: Introduction and Aim:Many etiological reasons are blamed for enuresis nocturna (EN). The aim of this study was to research prevalence and severity of EN among elementary school-age children and sociodemographic risk factors related to it.Materials and Methods:The study was performed in three elementary schools in Ankara, Turkey between January and May 2011. It was planned to have 2500 students of 6–14 ages in the study. The questionnaire, which consisted of questions, aiming to evaluate the EN condition of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
5
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
2
19
5
2
Order By: Relevance
“…In studies of 6- to 14-year-old children, 10% were reported to have nocturnal enuresis, and 2.8% were reported to have daytime urinary incontinence. 7 Daytime urinary incontinence is less prevalent than nocturnal enuresis and is typically resolved earlier in childhood. 2 Boys are more often affected by nocturnal enuresis, whereas girls are more often affected by daytime urinary incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of 6- to 14-year-old children, 10% were reported to have nocturnal enuresis, and 2.8% were reported to have daytime urinary incontinence. 7 Daytime urinary incontinence is less prevalent than nocturnal enuresis and is typically resolved earlier in childhood. 2 Boys are more often affected by nocturnal enuresis, whereas girls are more often affected by daytime urinary incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalensi enuresis pada laki-laki jauh lebih tinggi dibandingkan dengan anak perempuan dimana 91/140 pada laki-laki dan 49/140 pada perempuan (Solanki dan Desai, 2014). Doganer et al (2015) menyatakan bahwa ada perbedaan kejadian enuresis pada anak laki-laki dengan perempuan, dimana enuresis pada lakilakisebesar 10.7% dan 9.2% pada anak perempuan.…”
Section: Hasil Danunclassified
“…Aktigrafik analizin incelenmesinde; her iki grubun da günlük motor aktivite skorları benzerdi. Etkin uyku süresi MEN'li çocuklarda istatistiksel anlamda düşük olup; gece uyanıklık süresi, gün içi şekerleme sayısı ve parçalanma indeksinin MEN'li (15). Ailede enürezis nokturna öyküsü MEN'li grupta anlamlı derecede fazlaydı ve bu durum daha önce yapılmış araştırmalardakilere benzer şekilde enürezis nokturnanın genetik yatkınlıkla ilişkili olduğunu bir kere daha göstermiştir (3,16).…”
Section: Bulgularunclassified